Water quality of Boko-boko peat swamp based on physical-chemical parameters Langgam Village, Pelalawan Regency, Riau Province - Putra, Dasti Janarko; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The area around the Boko-Boko peat swamp has been used for palm plantation. Remains of fertilizer and pestiside used in the plantation may enter the water and decrease the water quality of the swamp. To understand the water quality of the Boko-Boko peat swamp’s waters, a research was conducted in March 2016. There were three sampling stations namely Station 1, Station 2, and Station 3 and in each station there were three sampling points, in the surface, 1.5 secchi and in the bottom. Samplings were conducted 3 times, once/week. Water quality parameters measured were depths, temperature, transparency, pH, DO, CO2, nitrate and phosphate. Results shown that depths was 70-250 cm, temperature: 30-31 oC, pH : 4-5, DO :0.35-3.28 mg/L, CO2: 4-21,97 mg/L, nitrate : 0.14-1.24 mg/L, and phosphate 0.01-0.17 mg/L. Nitrate concentration indicate that the Boko-Boko peat swamp was categorized as eutrophic, and phosphate concentration indicate that the Boko-Boko peat swamp is eutrophic.Keywords : peat swamp , Boko-Boko peat swamp, Water Quality, eutrophic.